Beyond attention: methylphenidate reduces dishonesty in healthy adults - Andreas Kappes; Alain Cohn; Michel André Maréchal; Anne-Marie Nussberger; Julian Savulescu; Philip Cowen; Michael Browning; M. J. Crockett (Psychopharmacology, 2026)
Rationale Healthy adults increasingly use drugs to enhance cognitive performance. However, these drugs influence brain systems that have also been associated with dishonesty. Given the prevalent use of potentially performance-enhancing drugs in contexts susceptible to cheating, it is crucial to ascertain whether they have adverse effects on honesty. Objectives Our primary objective was to compare the effects of methylphenidate with those of placebo to determine the direction and magnitude of its potential influence on dishonest behavior. We furthermore examined the intuitions of people who use smart drugs about the effects of methylphenidate on cheating in a US representative sample. Methods We conducted a double-blind, placebo-controlled experiment to compare the effects of methylphenidate (Ritalin), a popular performance-enhancing drug, and compared its effects with atomoxetine (Strattera), another performance-enhancing drug with a distinct pharmacological mechanism. Participants were randomly assigned to receive either a placebo ( n = 52), methylphenidate ( n = 49), or atomoxetine ( n = 50). Subsequently, they performed a die-rolling task in which they could increase their earnings by dishonestly misreporting their outcomes. Additionally, a representative sample of 575 American participants indicated their performance-enhancing drugs use and intuitions about the effects of these drugs on dishonesty. Results Our findings show that, compared to the placebo condition, methylphenidate reduced dishonesty. This effect was not attributable to statistical fluctuations, demand effects, or domain-general mechanisms such as mood or attention. In addition, individuals who use drugs to enhance performance have limited intuitions about the impact of methylphenidate on dishonest behavior. Conclusion These results reveal an unforeseen consequence associated with methylphenidate and may have policy implications regarding the paradoxical relationship between the use of drugs for performance enhancement and their potential impact on honesty.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Finding the sweet spot: a qualitative study exploring patients’ acceptability of chatbots in genetic service delivery - Stephanie Luca; Marc Clausen; Angela Shaw; Whiwon Lee; Suvetha Krishnapillai; Ella Adi-Wauran; Hanna Faghfoury; Gregory Costain; Rebekah Jobling; Melyssa Aronson; Eriskay Liston; Josh Silver; et al. (Human Genetics, 2023)

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

Inherited alterations of TGF beta signaling components in Appalachian cervical cancers - Thomas J. Knobloch; Juan Peng; Erinn M. Hade; David E. Cohn; Mack T. Ruffin; Michael A. Schiano; Byron C. Calhoun; William C. McBee; Jamie L. Lesnock; Holly H. Gallion; Jondavid Pollock; Bo Lu; et al. (Cancer Causes & Control, 2019)